“It’s more than a ride” veteran perceptions of peer specialist qualities and activities that were most valuable for post-incarceration reentry: a qualitative analysis - Eric Richardson; Kimberlee Flike; Justeen Hyde; Beth Ann Petrakis; D. Keith McInnes; Bo Kim (Health & Justice)
Abstract Background Reentry veterans experience many barriers to achieving physical and psychological well-being. While peer specialists can provide important support to veterans as they readjust to life post-incarceration, their specific activities and qualities most valued by veterans are not well known. The Post-Incarceration Engagement (PIE) intervention, coordinated with VA’s Health Care for Reentry Veterans (HCRV) program, links reentry veterans with a peer specialist who provides connection to services and social-emotional support during the reentry process. We conducted a qualitative examination of veterans’ perceptions regarding the key qualities and activities of peer specialists that were most valued during their reentry process. Methods We interviewed 25 veterans engaged in PIE about their experiences working with a PIE peer specialist. We conducted a thematic analysis. Two project team members independently coded interviews and identified emergent themes that were refined with input from other members. Results Veterans found the peer specialist’s physical and emotional availability, shared lived experience, and connection to resources to be invaluable for successful reentry post-incarceration. Veterans emphasized how important it was that the peer was consistently available and provided social, emotional, and logistical support. Secondly, veterans found it valuable to work with another veteran familiar with the VA system and to be able to share lived experiences. It provided an instant connection with the peer specialist. Finally, the personalized connections to VA and community resources equipped the reentry veterans with the essential resources to ensure continued success post-incarceration. Conclusion Reentry veterans identified several key qualities and activities of the peer specialist that were vital to their reentry success. Our results may be used to inform other interventions aimed at improving the lives of reentry veterans along with other reentry populations.